Non-State Armed Actors in the Middle East
XV, 278 p. 2 illus. in color.
Keywords: This volume investigates the nature and changing roles of the non-state armed groups in the Middle East with a special focus on Kurdish, Shia and Islamic State groups. To understand the nature of transformation in the Middle Eastern geopolitical space, it provides new empirical and analytical insights into the impact of three prominent actors, namely ISIS, YPG and Shia Militias. With its distinctive detailed and multi-faceted analyses, it offers new findings on the changing contours of sovereignty, geopolitics and ideology, particularly after the Arab Uprisings. Overall this volume contributes to the study of violent geopolitics, critical security studies and international relations particularly by exploring the ideologies and strategies of the new non-state armed actors.